STUDY OF CHEMICAL COMPOSITION AND ANTIMICROBIAL ACTIVITY OF PERIDERM OF POTATO TUBERS - E. O. Kulichenko; O. A. Andreeva; S. P. Lukashuk; M. V. Mazurina (Фармация и фармакология (Пятигорск), 2015)
The article presents the results of the studies of potato tubers periderm of Nevsky breed for the presence of some classes of biologically active substances, and also its antimicrobial activity of the alcohol extracts obtained from it.